Orange red inorganic pigment with near-infrared high reflection and infrared selective radiation characteristics as well as preparation method and application of orange red inorganic pigment
Through the combination of lithium, manganese and Re elements, an optimized preparation method is used to solve the problem of difficult to achieve high near-infrared reflectivity and infrared selective radiation characteristics in the prior art, and the preparation of efficient, environmentally friendly and beautiful orange-red inorganic pigments is achieved.
Patent Information
- Application Number
- CN202411653557.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art is difficult to achieve infrared selective radiation characteristics and ideal color performance while maintaining high near-infrared reflectivity, and the preparation process is complex and costly.
Using a combination of lithium (Li), manganese (Mn) and Re elements (Re is any one of Ti, Zr or Hf), an orange-red inorganic pigment with both near-infrared high reflection and infrared selective radiation characteristics is prepared through an optimized preparation method, including determination of stoichiometric ratio, ball milling, drying, calcining and screening.
It achieves high near-infrared reflectivity and infrared selective radiation characteristics, and has ideal color performance, avoids the use of toxic heavy metals, reduces production costs, and simplifies the preparation process.
Smart Images

Figure CN119529559A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of pigments, and in particular to a synergistic cooling orange-red pigment with near-infrared high reflection and infrared selective radiation characteristics and a preparation method thereof. Background Art
[0002] As global climate change and urban heat island effect become increasingly serious, the application demand of cooling materials in building energy conservation, military equipment and other fields continues to increase. Traditional cooling materials mainly include white and light-colored paints, which reduce surface temperature through high reflectivity. However, these materials often lack aesthetics and diversity, and it is difficult to meet the color requirements of different scenes. Therefore, the development of pigments with good cooling effect and rich colors has become a research hotspot. At present, the common colored cooling pigments on the market mainly include the following categories: 1) chromium pigments, such as chrome yellow (PbCrO4) described in patent CN108559280A, have bright colors, but contain heavy metals and pose environmental and health risks; 2) iron pigments, such as iron oxide red (Fe2O3) described in patent CN108713000A, have good environmental protection, but low near-infrared reflectivity and limited cooling effect; 3) composite oxide pigments, such as doped modified TiO2 described in patent CN1756805A, although they have a certain cooling effect, the color saturation is often insufficient. In addition, some studies have tried to improve the performance of pigments by doping with rare earth elements, but this usually requires a higher preparation temperature and consumes a lot of energy. In this context, it is of great significance to develop an orange-red pigment that has excellent cooling performance, ideal color, and environmental protection characteristics. In particular, how to achieve high near-infrared reflectivity while maintaining high far-infrared emissivity and good color performance is the main technical challenge currently faced. At the same time, simplifying the preparation process and reducing production costs are also issues that need to be urgently addressed. Summary of the invention
[0003] Purpose of the invention: The present invention aims to develop a new type of orange-red inorganic pigment with both near-infrared high reflection and infrared selective radiation characteristics through innovative material design and optimized preparation method, so as to meet the growing demand for high-performance colored cooling materials.
[0004] The technical problem that the present invention also aims to solve is to provide a preparation method and application of the above orange-red inorganic pigment.
[0005] In order to solve the above technical problems, the present invention discloses an orange-red inorganic pigment having both near-infrared high reflection and infrared selective radiation characteristics, wherein the orange-red inorganic pigment contains Li, Mn and Re elements, wherein the Re element is any one of Ti, Zr or Hf.
[0006] Specifically, when Re is Ti, the molar ratio range of Ti / (Mn + Ti) is 0.1 < x ≤ 0.8; when Re is Zr, the molar ratio range of Zr / (Mn + Zr) is 0.1 ≤ y ≤ 0.8; when Re is Hf, the molar ratio range of Hf / (Mn + Hf) is 0.1 ≤ z ≤ 0.8; wherein, the molar ratio of Li to (Mn + Re) is 1.5:1 to 2.5:1, preferably 2:1.
[0007] The present invention further provides a method for preparing the above orange - red inorganic pigment, which is characterized by comprising the following steps:
[0008] (1) Weigh raw materials containing Li source, Mn source and Re source according to the stoichiometric ratio;
[0009] (2) Mix and ball - mill the above raw materials;
[0010] (3) Dry and grind the ball - milled mixture; preferably, dry and grind the ball - milled mixture at 80°C;
[0011] (4) Calcinate the ground powder at 800 - 1000°C for 8 - 12 hours;
[0012] (5) Cool, grind and screen the calcined product to obtain the orange - red inorganic pigment with both near - infrared high - reflectance and infrared selective radiation characteristics.
[0013] Preferably, in step (2), anhydrous ethanol is used as the ball - milling medium, the ball - milling time is 6 - 8 hours, and the ball - milling speed is 300 - 400 rpm.
[0014] In step (5), a 200 - mesh sieve is used for sieving.
[0015] Wherein, the Li source is lithium carbonate, the Mn source is manganese carbonate, and the Re source is any one selected from titanium dioxide, zirconium dioxide, and hafnium dioxide.
[0016] The orange - red inorganic pigment prepared by the present invention can be adjusted within the range from red to orange - red.
[0017] When Re is Ti: (a) The near - infrared solar reflectance R of the pigment ≥ 64.5%; (b) The emissivity ε(λ) of the pigment in the 8 - 14 μm band ≥ 0.84; (c) In the CIE Lab color coordinates of the pigment, the range of L* is 59 - 68, the range of a* is 21 - 30, and the range of b* is 11 - 22.
[0018] When Re is Zr: (a) the near-infrared solar reflectivity R of the pigment is ≥77%; (b) the emissivity ε(λ) of the pigment in the 8-14 μm band is ≥0.84; (c) in the CIE Lab color coordinates of the pigment, the range of L* is 64-74, the range of a* is 22-31, and the range of b* is 18-25.
[0019] When Re is Hf: (a) the near-infrared solar reflectivity R of the pigment is ≥79%; (b) the emissivity ε(λ) of the pigment in the 8-14 μm band is ≥0.84; (c) in the CIE Lab color coordinates of the pigment, the range of L* is 66-77, the range of a* is 21-26, and the range of b* is 16-22.
[0020] The primary particle size of the orange-red inorganic pigment prepared by the invention is within the range of 100-500nm, and the secondary particle size is within the range of 0.5-5μm.
[0021] The present invention further proposes the use of the orange-red inorganic pigment in the preparation of building exterior wall coatings, automobile coatings or roof coatings.
[0022] The present invention also provides a coating composition, which comprises the above orange-red inorganic pigment.
[0023] Furthermore, the coating composition also includes a resin base and a solvent.
[0024] The present invention aims to develop a new type of orange-red inorganic pigment with both near-infrared high reflection and infrared selective radiation characteristics through innovative material design and optimized preparation method, so as to meet the growing demand for high-performance colored cooling materials.
[0025] The orange-red inorganic pigment with both near-infrared high reflection and infrared selective radiation characteristics of the present invention shows remarkable technological advancement, which is mainly reflected in the innovative material composition, excellent optical properties, excellent color performance, multi-element synergistic effect, flexible component regulation and simple and efficient preparation method.
[0026] Beneficial effects: The present application adopts this novel combination of lithium (Li), manganese (Mn) and Re elements (Re is at least one of Ti, Zr or Hf), which avoids the use of toxic heavy metals and is more environmentally friendly. Through the synergistic effect of Li, Mn and Re elements, the unity of high reflectivity, high emissivity and ideal color is achieved. Compared with traditional pigments with a single component, this combination has better optical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0028] Figure 1 Reflection spectra of a series of samples in Example 1: (a) 0.2-2.5 μm; (b) 2.5-25 μm;
[0029] Figure 2 Reflection spectra of the samples in Example 2: (a) 0.2-2.5 μm; (b) 2.5-25 μm;
[0030] Figure 3 The reflection spectra of the samples in Example 3 are as follows: (a) 0.2-2.5 μm; (b) 2.5-25 μm;
[0031] Figure 4 Reflection spectra of the samples of Example 4: (a) 0.2-2.5 μm; (b) 2.5-25 μm;
[0032] Figure 5 Reflection spectra of the samples of Example 5: (a) 0.2-2.5 μm; (b) 2.5-25 μm;
[0033] Figure 6 Reflection spectra of the samples in Example 6: (a) 0.2-2.5 μm; (b) 2.5-25 μm. DETAILED DESCRIPTION
[0034] Embodiment 1:
[0035] Li2CO3, MnO2 and TiO2 powders were weighed according to the stoichiometric ratio of 1:1-x:x (x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8), placed in a polytetrafluoroethylene ball mill, and zirconia balls of different particle sizes (small particle size: medium particle size: large particle size = 1:1:5) were added, with a ball-to-material ratio of 5:1. An appropriate amount of anhydrous ethanol was added as a ball milling medium, and the mixture was ball milled at a speed of 300rpm for 6h. The obtained mixture was filtered, and the mixed sample obtained by filtration was placed in an oven at 80°C for drying, and the dried block sample was ground into powder; the mixed powder was placed in a muffle furnace and sintered at 900°C for 10h. The sample was taken out after cooling to below 100°C with the furnace, and the sintered powder was ground and sieved (200 mesh) to obtain orange-red powder Li2Mn 1-x Ti xO3 (abbreviated as LMT-x, x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, pure Li2MnO3 abbreviated as LMO). The product performance parameters involved in Example 1 are shown in Table 1. All pigments show high infrared emissivity (ε(λ)>83.70%), which is higher than the commercially available iron red pigment (ε(λ)=83.19%). The sample with the highest emissivity, LMT-0.6, can reach 85.77%.
[0036] Table 1: Product performance parameters of Example 1
[0037]
[0038] Example 2
[0039] Li2CO3, MnO2 and ZrO2 powders were weighed according to the stoichiometric ratio of 1:1-y:y (y=0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8), put into a polytetrafluoroethylene ball mill, and zirconia balls of different particle sizes (small particle size: medium particle size: large particle size = 1:1:5) were added with a ball-to-material ratio of 5:1. Anhydrous ethanol was added as the ball milling medium, and the ball milling was carried out at a speed of 300 rpm for 6 hours. The obtained mixture was filtered, and the mixed sample obtained by filtration was placed in an oven at 80°C for drying, and the dried block sample was ground into powder; the mixed powder was placed in a muffle furnace and sintered at 900°C for 10 hours, and the sample was taken out after cooling to below 100°C with the furnace, and the sintered powder was ground and sieved (200 mesh) to obtain Zr-doped Li2MnO3 mixed phase orange-red powder pigment (abbreviated as Mn 1-y Zr y , y=0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8). The product performance parameters involved in Example 2 are shown in Table 2.
[0040] Table 2: Product performance parameters of Example 2
[0041]
[0042] Embodiment 3:
[0043] Li2CO3, MnO2 and HfO2 powders were weighed according to the stoichiometric ratio of 1:1-z:z (z==0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8), put into a polytetrafluoroethylene ball mill, add zirconia balls of different particle sizes (small particle size: medium particle size: large particle size = 1:1:5), the ball-to-material ratio was 5:1, anhydrous ethanol was added as the ball milling medium, and the ball milling was carried out at a speed of 300rpm for 6h. The obtained mixture was filtered, and the mixed sample obtained by filtration was placed in an oven at 80℃ for drying, and the dried block sample was ground into powder; the mixed powder was placed in a muffle furnace and sintered at 900℃ for 10h, and the sample was taken out after cooling to below 100℃ with the furnace, and the sintered powder was ground and sieved (200 mesh) to obtain Hf-doped Li2MnO3 mixed phase orange-red powder pigment (abbreviated as Mn 1-z Hf z , z=0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8). The product performance parameters involved in Example 3 are shown in Table 3.
[0044] Table 3: Product performance parameters of Example 3
[0045]
[0046]
[0047] Embodiment 4:
[0048] The ground LMT-x (x = 0.2, 0.4, 0.6, 0.8) pigments and fluorocarbon resin were placed in a polytetrafluoroethylene ball mill in a mass ratio of (1:10), and zirconium oxide balls of different particle sizes (small particle size: medium particle size: large particle size = 1:1:5) were added. The ball-to-material ratio was 5:1. The ball was milled at a speed of 300 rpm for 3 h to ensure that the pigment was completely dispersed in the resin. Then, a 200 μm coating rod was used to apply the coating on an aluminum plate (4 cm * 4 cm * 1 mm) and dried at room temperature for 12 h. Its cooling performance was tested.
[0049] The cooling performance of the composite material was tested by a self-designed device using a thermal measurement method. Depending on the experimental environment, the thermal measurement can be divided into two methods: indoor thermal measurement and room temperature thermal measurement. The indoor thermal measurement was performed using a solar simulator at an ambient temperature of 26°C. The composite coating was evenly coated on an aluminum alloy sheet with a size of 4cm*4cm*1mm and covered on a polytetrafluoroethylene mold (7.5cm*7.5cm*5cm) with a circular groove of 2.5cm*2.5cm hollowed out on the top. The 94043A infrared lamp from Newport, Germany, was used to simulate sunlight irradiation. The coating was exposed to simulated sunlight for 4 hours. A K-type thermocouple was fixed 1.5cm below the center of the aluminum sheet to measure the temperature change caused by infrared absorption in the cavity, and the temperature change was recorded every 1min. The outdoor thermal measurement was conducted in Shenzhen, China (22°N, 114°E; November 21 to November 24, 2023). The coating was directly exposed to sunlight and air using the same test device as the indoor thermal measurement. The coating samples involved in Example 4 are recorded as LMT-0.2, LMT-0.4, LMT-0.6, and LMT-0.8, and their performance parameters are shown in Table 4.
[0050] Table 4: Product performance parameters of Example 4
[0051]
[0052] Embodiment 5:
[0053] The ground Mn 1-y Zr y The pigments (y=0.2, 0.4, 0.6, 0.8) and fluorocarbon resins were put into a polytetrafluoroethylene ball mill in a mass ratio of (1:10), and zirconium oxide balls of different particle sizes (small particle size: medium particle size: large particle size=1:1:5) were added. The ball-to-material ratio was 5:1. The ball milling was carried out at a speed of 300 rpm for 3 h to ensure that the pigment was completely dispersed in the resin. Then, a 200 μm coating rod was used to apply the coating on an aluminum plate (4 cm*4 cm*1 mm), and the coating was dried at room temperature for 12 h. The cooling performance was tested.
[0054] The cooling performance of the composite material was tested by a self-designed device using a thermal measurement method. Depending on the experimental environment, the thermal measurement can be divided into two methods: indoor thermal measurement and room temperature thermal measurement. The indoor thermal measurement was performed using a solar simulator at an ambient temperature of 26°C. The composite coating was evenly coated on an aluminum alloy sheet with a size of 4cm*4cm*1mm and covered on a polytetrafluoroethylene mold (7.5cm*7.5cm*5cm) with a circular groove of 2.5cm*2.5cm hollowed out on the top. The 94043A infrared lamp from Newport, Germany, was used to simulate sunlight irradiation. The coating was exposed to simulated sunlight for 4 hours. A K-type thermocouple was fixed 1.5cm below the center of the aluminum sheet to measure the temperature change caused by infrared absorption in the cavity, and the temperature change was recorded every 1min. The outdoor thermal measurement was conducted in Shenzhen, China (22°N, 114°E; November 21 to November 24, 2023). The coating was directly exposed to sunlight and air using the same test device as the indoor thermal measurement. The samples involved in Example 5 are denoted as LMZ-0.2, LMZ-0.4, LMZ-0.6, and LMZ-0.8, and their performance parameters are shown in Table 5.
[0055] Table 5: Product performance parameters of Example 5
[0056]
[0057]
[0058] Embodiment 6:
[0059] The ground Mn 1-z Hf z The pigments (z=0.2, 0.4, 0.6, 0.8) and fluorocarbon resins were put into a polytetrafluoroethylene ball mill in a mass ratio of (1:10), and zirconium oxide balls of different particle sizes (small particle size: medium particle size: large particle size = 1:1:5) were added. The ball-to-material ratio was 5:1. The ball milling was carried out at a speed of 300 rpm for 3 h to ensure that the pigment was completely dispersed in the resin. Then, a 200 μm coating rod was used to apply the coating on an aluminum plate (4 cm*4 cm*1 mm), and the coating was dried at room temperature for 12 h. The cooling performance was tested.
[0060] The cooling performance of the composite material was tested by a self-designed device using a thermal measurement method. Depending on the experimental environment, the thermal measurement can be divided into two methods: indoor thermal measurement and room temperature thermal measurement. The indoor thermal measurement was performed using a solar simulator at an ambient temperature of 26°C. The composite coating was evenly coated on an aluminum alloy sheet with a size of 4cm*4cm*1mm and covered on a polytetrafluoroethylene mold (7.5cm*7.5cm*5cm) with a circular groove of 2.5cm*2.5cm hollowed out on the top. The 94043A infrared lamp from Newport, Germany, was used to simulate sunlight irradiation. The coating was exposed to simulated sunlight for 4 hours. A K-type thermocouple was fixed 1.5cm below the center of the aluminum sheet to measure the temperature change caused by infrared absorption in the cavity, and the temperature change was recorded every 1min. The outdoor thermal measurement was conducted in Shenzhen, China (22°N, 114°E; November 21 to November 24, 2023). The coating was directly exposed to sunlight and air using the same test device as the indoor thermal measurement. The samples involved in Example 6 are denoted as LMH-0.2, LMH-0.4, LMH-0.6, and LMH-0.8, and their performance parameters are shown in Table 6.
[0061] Table 6: Product performance parameters of Example 6
[0062]
[0063]
[0064] In summary,
[0065] When Re is Ti: (a) the near-infrared solar reflectivity R of the pigment is ≥ 64.5%; (b) the emissivity ε(λ) of the pigment in the 8-14 μm band is ≥ 0.84; (c) in the CIE Lab color coordinates of the pigment, the range of L* is 59-68, the range of a* is 21-30, and the range of b* is 11-22.
[0066] When Re is Zr: (a) the near-infrared solar reflectivity R of the pigment is ≥77%; (b) the emissivity ε(λ) of the pigment in the 8-14 μm band is ≥0.84; (c) in the CIE Lab color coordinates of the pigment, the range of L* is 64-74, the range of a* is 22-31, and the range of b* is 18-25.
[0067] When Re is Hf: (a) the near-infrared solar reflectivity R of the pigment is ≥79%; (b) the emissivity ε(λ) of the pigment in the 8-14 μm band is ≥0.84; (c) in the CIE Lab color coordinates of the pigment, the range of L* is 66-77, the range of a* is 21-26, and the range of b* is 16-22.
[0068] The primary particle size of the orange-red inorganic pigment prepared by the invention is within the range of 100-500nm, and the secondary particle size is within the range of 0.5-5μm.
[0069] The present invention provides a preparation idea and method of an orange-red inorganic pigment having both near-infrared high reflection and infrared selective radiation characteristics. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. An orange-red inorganic pigment having both near-infrared high reflection and infrared selective radiation characteristics, characterized in that: The orange-red inorganic pigment contains Li, Mn, and Re elements, where the Re element is any one of Ti, Zr, or Hf.
2. The orange-red inorganic pigment according to claim 1, characterized in that When Re is Ti, the molar ratio of Ti / (Mn + Ti) ranges from 0.1 < x ≤ 0.8; when Re is Zr, the molar ratio of Zr / (Mn + Zr) ranges from 0.1 ≤ y ≤ 0.8; when Re is Hf, the molar ratio of Hf / (Mn + Hf) ranges from 0.1 ≤ z ≤ 0.8; where the molar ratio of Li to (Mn + Re) is 1.5:1 to 2.5:
1.
3. The method for preparing the orange-red inorganic pigment according to claim 1, characterized in that: It includes the following steps: (1) Weigh the raw materials containing Li source, Mn source, and Re source according to the stoichiometric ratio. (2) Mix and ball-mill the above raw materials. (3) Dry and grind the ball-milled mixture. (4) Calcinate the ground powder at 800 - 1000 °C for 8 - 12 hours. (5) Cool, grind, and sieve the calcined product to obtain the orange-red inorganic pigment with both high near-infrared reflectivity and infrared selective radiation characteristics.
4. The preparation method according to claim 3, characterized in that: In step (2), anhydrous ethanol is used as the ball-milling medium, the ball-milling time is 6 - 8 hours, and the ball-milling speed is 300 - 400 rpm.
5. The preparation method according to claim 3, characterized in that: In step (5), a 200-mesh sieve is used for sieving.
6. The preparation method according to claim 3, characterized in that: The Li source is lithium carbonate, the Mn source is manganese carbonate, and the Re source is any one selected from titanium dioxide, zirconium dioxide, and hafnium dioxide.
7. Use of the orange-red inorganic pigment according to claim 1 in the preparation of architectural exterior wall coatings, automotive coatings, or roof coatings.
8. A coating composition, characterized in that The coating composition contains the orange-red inorganic pigment according to claim 1.
9. The coating composition according to claim 8, characterized in that The coating composition further includes a resin binder.
Citation Information
Patent Citations
Wear-resisting colored asphalt
CN108559280A
Preparation of red iron oxide pigment
CN108713000A
Zirconium adulterated lithium manganate anode film material and its making method
CN101034741A
False-proof ink having obvious contrast for absorption / reflection of different-waveband infrared lights
CN101225265A
Lithium-containing transition metal oxide coated and doped positive electrode material and preparation method thereof
CN116169283A
Cited By
A highly saturated red inorganic pigment, its preparation method and application
CN122941206A